A Primer on Sustainability - Whitfield, Ronald (Business Expert Press, 2014)
Ebook from IG Library ; This book takes a broad look at the ways in which the concept of sustainability is being applied in the business context. It answers the question, 'What does Sustainability mean to the way we practice business?'